Navigating Village Credit Institutions Based On Sad Kerthi Loka Bali In Buleleng Regency - I Made Mai Noval; A.A.N Oka Suryadinatha Gorda; A.A.N Eddy Supriadinata Gorda (Jurnal Keuangan dan Perbankan, 2022)
This study examines how the village credit institution implements the local wisdom of Sad Kerthi in the form of the vision of "Nangun Sad Kerthi Loka Bali" and how the vision can help maintain the existence of LPD in the future. This phenomenon is important to study considering the magnitude of the benefits that can be given by the Village Credit Institution for the development and development of the rural economy sector. This research was conducted using qualitative methods, as well as data analysis techniques using interactive analysis techniques, and data collection techniques in the study through interviews, observation, and documentation. This research was conducted at 9 LPD in Buleleng Regency. This study found that the implementation of local wisdom of Sad Kerthi in LPD, of the six concepts of the existing Local Wisdom, 4 concept of local wisdom Sad Kerthi could already be well implemented by LPD. And the local wisdom of Sad Kerthi in the form of the vision was able to contribute to the sustainability of the LPD through conservation of custom villages and was able to create a sturdy economic pattern within the scope of traditional villages, and this economic pattern would also help maintain LPD's existence through sustainable performance results. The results of this study were able to contribute to all village credit institutions in the province of Bali as an effort to maintain its existence